UZBEKISTAN SOCIAL STATE: STATE CONTROLLED SOCIAL PROTECTION AND SOCIAL ASSISTANCE (Academicia Globe: Inderscience Research, 2024)
This prepared article describes the wide-scale work being carried out in the field of social protection and social assistance in our republic today, especially the National Agency for Social Protection under the President of the Republic of Uzbekistan, which was established as a proof that Uzbekistan declared itself a social state to the world, and its activities in accordance with international standards.Also, not only social assistance, but also provision of education, upbringing, material and spiritual assistance and medical services to the population in need of social protection is envisaged.